Development and validation of the Kilifi Stigma Scale for Epilepsy in Kenya. - Mbuba, C; Abubakar, A; Odermatt, P; Newton, C; Carter, J (2012)
The aim of this study was to develop and validate a tool to measure perceived stigma among people with epilepsy (PWE) in Kilifi, Kenya. We reviewed existing scales that measured stigma, particularly of epilepsy. We conducted a qualitative study to determine salient concerns related to stigma in Kilifi. Themes were generated, and those related to stigma were used to construct an 18-item stigma scale. A descriptive cross-sectional survey was then conducted among 673 PWE to assess the reliability and validity of the scale. Internal consistency was calculated using Cronbach's alpha and test-retest reliability with an interclass correlation coefficient. The final scale had 15 items, which had high internal consistency (Cronbach's α=0.91) and excellent test-retest reliability (r=0.92). Factor analysis indicated that the scale was unidimensional with one factor solution explaining 45.8% of the variance. The Kilifi Stigma Scale for Epilepsy is a culturally appropriate measure of stigma with strong psychometric properties.